Please touch! explore the evolving world of touchscreen technology - Philipp, Hal (Electronic Design, 2008)
You've probably encountered some faulty touch-screens that required multiple touches, applying more pressure each time, just to register an entry. That's because early resistive touchscreen technologies were environmentally unstable and subject to a variety of wearout mechanisms. Today's touchscreens, however, are a joy to use. Their technology underpins attractive and responsive interfaces that are easy to modify for additional functionality Modifications often are a matter of software changes, and the latest touchscreens operate reliably even in RF-polluted environments.